2022
DOI: 10.1002/nop2.1472
|View full text |Cite
|
Sign up to set email alerts
|

Effect of digital detox program on electronic screen syndrome among preparatory school students

Abstract: School students are our greatest asset and our hope for the future.Moreover, the stage of childhood represents the foundation for future life. Adolescence is the phase of life, extending between childhood and adulthood; Egypt's population of young people is growing dramatically. About 17 million teenagers (10 to 19 years old) make up roughly 19% of the population (UNICEF Egypt, n.d.).Electronic screens have increased widely among all people without any age barriers. Devices with screens (TV, Smart Phone, Table… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…Also, this result was approved by (Mohamed et al, 2023) who study revealed that a notable portion of participants' parents were employed, with a clear distinction between fathers and mothers. Fathers were more likely to be employed, while a significant portion of mothers appeared to be homemakers.…”
Section: Table (5)mentioning
confidence: 75%
“…Also, this result was approved by (Mohamed et al, 2023) who study revealed that a notable portion of participants' parents were employed, with a clear distinction between fathers and mothers. Fathers were more likely to be employed, while a significant portion of mothers appeared to be homemakers.…”
Section: Table (5)mentioning
confidence: 75%
“…Digital-free tourism has also become an emerging solution for family and social engagements [ 82 ]. A digital detox program in 2 preparatory governmental schools in Egypt indicated positive results; the high rate of screen addiction among students dropped to 14.3% in the posttest measures compared with 20% in the pretest measures [ 83 ].…”
Section: Discussionmentioning
confidence: 99%